Ocean‐Wave‐Atmosphere Interaction Processes in a Fully Coupled Modeling System - Lichuan Wu; Øyvind Breivik; Anna Rutgersson (Journal of Advances in Modeling Earth Systems, 2019)
Abstract A high‐resolution coupled ocean‐wave‐atmosphere model (Uppsala University Coupled model, UU‐CM) of the Baltic Sea and the North Sea with improved representation of ocean‐wave‐atmosphere interaction processes is presented. In the UU‐CM model, the stress on the air‐sea interface is estimated as a balance of four stress terms, that is, the air‐side stress, ocean‐side stress, wave‐supported stress (absorption of momentum by the wave field), and the momentum flux from waves to currents (breaking waves). The vector differences between these four stress terms are considered in the coupled system. The turbulent kinetic energy flux induced by wave breaking, the Stokes‐Coriolis force and the Stokes drift material advection terms are added to the ocean circulation model component. Based on two‐month‐long (January and July) simulations, we find that the ocean‐wave‐atmosphere coupling has a significant influence on coastal areas. The coupled system captures the influence of surface currents and local systems such as coastal upwelling and their impact on the atmosphere. The wave‐current interaction enhances the upper ocean mixing and reduces the sea surface temperature in July significantly. However, the pattern of the wave‐current processes influences on the ocean current and waves are complex due to the stress differences in both magnitude and direction.